2014
DOI: 10.3855/jidc.4228
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of susceptibility to conventional first line drugs in Salmonella isolates from enteric fever patients in Nepal

Abstract: Introduction: Enteric fever is endemic in Nepal and poses a significant public health burden. The first-line drugs ampicillin, chloramphenicol, and cotrimoxazole have not been part of empirical therapy for two decades due to the development of multidrug-resistant Salmonella strains. The objective of this study was to determine the antibiogram pattern of Salmonella serovars isolated from the blood of clinically suspected enteric fever patients. Methodology: A cross sectional study was carried out in a tertiary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
53
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 25 publications
10
53
2
Order By: Relevance
“…All (100%) Salmonella paratyphi A were resistant to nalidixic acid in this study which is similar to other studies in India and Nepal 17,20 . Dissimilarity was noted by Shetty et al (2012) in India who reported 62.5% Salmonella paratyphi A were resistant to nalidixic acid.…”
Section: Resultssupporting
confidence: 81%
“…All (100%) Salmonella paratyphi A were resistant to nalidixic acid in this study which is similar to other studies in India and Nepal 17,20 . Dissimilarity was noted by Shetty et al (2012) in India who reported 62.5% Salmonella paratyphi A were resistant to nalidixic acid.…”
Section: Resultssupporting
confidence: 81%
“…Recently, reports from around the world including our country have shown the re-emergence of in vitro susceptibility in the Salmonella against the aforementioned first-line drugs 4. Our previous trial comparing gatifloxacin with chloramphenicol showed excellent efficacy of chloramphenicol in the treatment of enteric fever 5.…”
Section: Discussionmentioning
confidence: 96%
“…A signifi cant decrease in resistance to chloramphenicol and cotrimoxazole has also been reported from Nepal 11,16,18 . Decrease in resistance may again make these antibiotics useful in near future.…”
Section: Chloramphenicol Cotrimoxazole Ampicillinmentioning
confidence: 92%